2020
DOI: 10.1371/journal.pone.0237615
|View full text |Cite
|
Sign up to set email alerts
|

Use of somatic cell count as an indicator of colostrum quality

Abstract: The impact of cow mammary gland diseases on the quality of colostrum is not conclusively defined; research results are conflicting. However, it is widely believed that mastitis lowers the level of immunoglobulins and the quality of the colostrum produced. Therefore, the aim of this study was to determine the influence of somatic cell counts (SCC) on the colostrum immunostimulating and chemical components. The experiment was conducted on an experimental organic dairy farm in which a herd of approximately 250 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
1
17
1
3
Order By: Relevance
“…Moreover, Cabral et al (2016) referred to the importance of using teat sealants and antibiotics at dry off to avoid mastitis during dry periods, which can diminish colostrum quality. Puppel et al (2020) concluded that the SCC of the first milking colostrum could be used as an indicator of colostrum quality. They found nearly double the concentration of first colostrum immunoglobulins in cows with SCC ≥ 400,000 cells/mL than in colostrum from cows with SCC ≤ 400,000 cells/ mL.…”
Section: Season Of Calvingmentioning
confidence: 99%
“…Moreover, Cabral et al (2016) referred to the importance of using teat sealants and antibiotics at dry off to avoid mastitis during dry periods, which can diminish colostrum quality. Puppel et al (2020) concluded that the SCC of the first milking colostrum could be used as an indicator of colostrum quality. They found nearly double the concentration of first colostrum immunoglobulins in cows with SCC ≥ 400,000 cells/mL than in colostrum from cows with SCC ≤ 400,000 cells/ mL.…”
Section: Season Of Calvingmentioning
confidence: 99%
“…The concentration of colostrum immunoglobulins (Ig) varies with the cow’s health status 1 , amount of colostrum produced, calving season 2 , breed, age 3 , 4 , production system 5 , length of non-lactating period 6 , prepartum milking 7 , time delay between parturition and first milking 8 , 9 , and heat stress 10 . Additionally, increased levels of Ig were demonstrated in cows inoculated with vaccines containing E. coli , Coronavirus and Rota antigens 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The quality and quantity of cows’ mammary gland secretions are closely related to udder health. Puppel et al 1 reported that in colostrum from the first milking, the IgG concentration was two-fold greater and the C18:2 cis9trans11 three-fold greater in colostrum with somatic cell count (SCC) ≤ 400 000 cells/ml, than in colostrum with ≥ 400 000 cells/ml. It should be emphasized that fatty acids, are antibacterial agents that destabilize bacterial cell membranes 24 , due to their amphipathic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Οι Gulliksen et al (2008) διαπίστωσαν ότι οι αγελάδες με αριθμό σωματικών κυττάρων >50.000/mL γάλατος στον πρώτο έλεγχο γαλακτοπαραγωγής (μεταξύ 8ης και 65ης ημέρας) είχαν περισσότερες πιθανότητες να παράγουν πρωτόγαλα με συγκέντρωση IgG <30 g/L σε σύγκριση με εκείνες που είχαν μικρότερο αριθμό σωματικών κυττάρων. Επιπλέον, οι Puppel et al (2020) διαπίστωσαν ότι οι αγελάδες οι οποίες είχαν ≤400.000 σωματικά κύτταρα/mL στο πρωτόγαλα, εμφάνισαν διπλάσια συγκέντρωση ανοσοσφαιρινών σε σύγκριση με εκείνες που είχαν >400.000 σωματικά κύτταρα/mL. Συνεπώς συμπέραναν ότι ο αριθμός των σωματικών κυττάρων στο πρωτόγαλα μπορεί να αποτελέσει έναν ενδεικτικό παράγοντα της ποιότητάς του.…”
Section: δ10 μολυνση του μαστουunclassified
“…Η υγιεινή του μαστού αποτελεί επίσης έναν παράγοντα που θα μπορούσε να επηρεάσει τη σύνθεσή του. Οι Puppel et al (2020) διαπίστωσαν ότι οι αγελάδες οι οποίες είχαν ≤400.000 σωματικά/mL στο πρωτόγαλα, εμφάνισαν διπλάσια συγκέντρωση ανοσοσφαιρινών στο πρωτόγαλα σε σύγκριση με εκείνες που είχαν >400.000 σωματικά κύτταρα/mL. Συνεπώς συμπέραναν ότι ο αριθμός των σωματικών κυττάρων στο πρωτόγαλα μπορεί να αποτελέσει έναν ενδεικτικό παράγοντα της ποιότητάς του.…”
Section: γ η εκτροφη ως παραγοντας που επηρεαζει τη συνθεση και την ποιοτητα του πρωτογαλατοςunclassified